Taman Penitipan Anak Yudhistira Batuan Sebagai Wahana Pengasuhan Anak Usia Dini Bagi Orang Tua Karier - Sari, Ni Putu Mulia; Punia, I Nengah; Astika, Ketut Sudhana (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRAK Parents’ bustle in their jobs make the role and function as parents must be replaced by other people. Particularly the busy parents who have toddlers that need particular attention and surveillance especially in embedding good attitude, because embedding good attitude is truly prominent for children’s growth and progress. Children care Yudhistira Batuan is one of daycares located in Jungut subvillage, Batuan village, Sukawati district, Gianyar regency, this place is chosen by the busy parents to commend their children. Through children care Yudhistira Batuan, children’s progress is more directed and they will be able to be more independent. Children care Yudhistira Batuan has planned nurture with balanced system of learning and playing, hence, the busy parents choose children care Yudhistira Batuan as an oppropriate choice and this action will be able to give positive impacts for their toddlers as well. Keyword: busy parents, the important of embedding good attitude, children care